Keter : The Crown of God in Early Jewish Mysticism - Green, Arthur, 1941- (Book collections on Project MUSE., 1997)
Keter is a close reading of fifty relatively brief Jewish texts, tracing the motif of divine coronation from Jewish esoteric writings of late antiquity to the Zohar, written in thirteenth-century Spain. In the course of this investigation Arthur Green draws a wide arc including Talmudic, Midrashic, liturgical, Merkavah, German Hasidic, and Kabbalistic works, showing through this single theme the spectrum of devotional, mystical, and magical views held by various circles of Jews over the course of a millennium or more. The first portion of the work deals with late antiquity, emphasizing the close relationship between texts of what is often depicted as "normative" Judaism and their mystical/magical analogues. The mythic imagination of ancient Judaism, he suggests, is shared across this spectrum. The latter portion of the work turns to the medieval Jews who inherited this ancient tradition and its evolution into Kabbalah, where keter plays a key role as the first of the ten divine emanations or sefirot. The nature of these sefirot as symbols and the emergence of a structured and hierarchical symbolism out of the mythic imagery of the past are key themes in these later chapters. As a whole, Keter takes the reader on an exciting tour of the interior landscapes of the Jewish imagination, offering some remarkable insights into the nature of mystical and symbolic thinking in the Jewish tradition. Originally published in 1997. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905